A study on static voltage collapse proximity indicators - Verayiah R.; Abidin I.Z. (2023)
In the time of rapid growth, there is an increase of demand for a reliable and stable power supply. Due to this, utility companies are forced to operate their power system nearer to its maximum capabilities since system expansion may be a costly option. As a result, the power system will be at risk to voltage collapse. Voltage collapse phenomenon is known to be complex and localised in nature but with a widespread effect. The ultimate effect of voltage collapse would be total system collapse which would incur high losses to utility companies. Thus, online monitoring of power system stability has become a vital factor for electric utility companies.This paper looks into combining a power flow program in MATLAB environment with two line stability indices, which are Fast Voltage Stability Index (FVSI) and Line Stability Index, LQP for automatic contingency ranking. The IEEE 14 Bus Test System is used as a standard test system. This approach investigates each line of the system through calculating an indicator that varies from zero (no load condition) to unity (maximum permissible loading condition). The basic concept of maximum power transfer through a line is utilized. Correlation study on the results obtained from contingency ranking and voltage stability analysis were conducted and it is found that line outages at the weak lines would cause voltage instability condition to a system. Subsequently, using the result from the contingency ranking, weak areas in the system can be identified. Verification of this technique with other existing technique shows a strong agreement between them. 2008 IEEE.